The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.2214/ajr.11.7701
|View full text |Cite
|
Sign up to set email alerts
|

Is Confidence of Mammographic Assessment a Good Predictor of Accuracy?

Abstract: OBJECTIVE Interpretive accuracy varies among radiologists, especially in mammography. This study examines the relationship between radiologists’ confidence in their assessments and their accuracy in interpreting mammograms. MATERIALS AND METHODS In this study, 119 community radiologists interpreted 109 expert-defined screening mammography examinations in test sets and rated their confidence in their assessment for each case. They also provided a global assessment of their ability to interpret mammograms. Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Our results are comparable to studies on uncertainty in the assessment of mammography images . A low annual volume of mammography assessments leads to a higher frequency of low confidence score and lower negative predictive values in a group of radiologists.…”
Section: Discussionsupporting
confidence: 81%
“…Our results are comparable to studies on uncertainty in the assessment of mammography images . A low annual volume of mammography assessments leads to a higher frequency of low confidence score and lower negative predictive values in a group of radiologists.…”
Section: Discussionsupporting
confidence: 81%
“…As this dataset contains the independent assessments by multiple radiologists of the same mammogram (mean number of independent readings per mammogram = 92), and the true status of each mammogram ( S1 Text ), it allows us to investigate the performance of the above CI-rules. We stress that, while the above dataset has recently been used to investigate the performance of individual radiologists [ 29 31 ], up to now, its potential to investigate CI in mammography screening has not yet been harnessed.…”
Section: Methodsmentioning
confidence: 99%
“…can nonetheless demonstrate significant selfmonitoring ability ('Will I get THIS question right?'). 9 Self-monitoring has also been shown to correlate with accuracy in radiograph interpretation 10,11 (Table 1).…”
Section: Conceptual Modelmentioning
confidence: 99%
“…Eva and Regehr showed that psychology students who have relatively poor self‐assessment ability for a certain knowledge domain (‘Can I predict the number of questions I will get right on this examination?’) can nonetheless demonstrate significant self‐monitoring ability (‘Will I get THIS question right?’) . Self‐monitoring has also been shown to correlate with accuracy in radiograph interpretation (Table ).…”
Section: Introductionmentioning
confidence: 98%